Propagation of the Sidoardjo mud in the Porong River, East Java, Indonesia - Andika, Neil, author; Julien, Pierre Y., advisor; Grigg, Neil S., committee member; Ettema, Robert, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2021)
The Sidoarjo Mud Volcano in East Java, Indonesia erupted on May 29, 2006. It caused controversy because of the impact of the mud volcano had on communities around it. The discharge of the mud volcano was 50,000 m3/d (Harnanto, 2011) which comprised a 35% concentration of silt and clay. To mitigate the damage to surrounding regions, the Government of Indonesia diverted the mud to Madura Strait through the Porong River in 2016 (Hadimuljono, 2008). The objectives of this thesis are to: (1) understand the physical properties of mud from the mud volcano and its interaction with the water in the river; (2) carry out field measurements of sediment concentration along the Porong River for a model validation; (3) determine how the concentration of mud from the mud volcano varies along the river; (4) create a framework or guideline for the mitigation of a mud volcano disaster in the future. Laboratory experiments were used to test the sediment properties. The experiments of turbidity and sediment concentration, C, concluded that the linear regression, C=5.297×Turbidity+24, was the best fitted regression. Flocculation tests in 2019 showed that the recorded deflocculated settling velocity for the sample of the Ginonjo Outlet was 0.013 mm/s which was approximately 2 times slower than the natural settling velocity of 0.028 mm/s. This value was one order slower than the general settling velocity for flocculated particles. Two field measurement programs were completed, in July 2018 and in September 2019. The field programs in 2018 observed the sediment concentration along the Porong River at 106 cross-sections and the point source sediment concentration at Ginonjo Outlet was 57,000 mg/l. It was found that the observed maximum sediment concentration ranged between 691 mg/l and 4,198 mg/l. The average sediment concentration at the downstream end of the Porong River on the other hand was 90 mg/l. The field program in 2019 captured the vertical sediment concentration profiles of the first 4 km of the Porong River. The highest near-bed sediment concentration was 1,500 mg/l at Line C cross-section 9. This was followed by 1,450 mg/l at Line C cross-section 6. These measurements showed that the sediment concentration are uniform along the Porong River except for the first 4 km where the bottom sediment concentration are higher. There are three flow conditions based on the hydrograph of the Porong River: low flow with 45 m3/s, medium flow with 250 m3/s, and high flow with 2500 m3/s. For low flow, the average flow velocity was 0.12 m/s and the shear velocity was 0.01 m/s. Results from the two-dimensional mixing model without settling was the fully-mixed concentration for low flow condition achieved at 4 km downstream from the outlet with a concentration of 470 mg/l. There was 380 mg/l difference between the model's result and the observed concentration. The two-dimensional mixing and setting model without flocculation produced a result of sediment concentration of 195 mg/l at the downstream end of the Porong River. This came from the clay fraction which was about 48% of the total sediment. The sediment concentration difference between this model and the observed data was 105 mg/l. The two-dimensional mixing and setting model with flocculation was then used. The sediment concentration at the left bank side of the Porong River was about 90 mg/l, which matched the observed data. The gravel, sand and coarser silt fractions settled at the first 4 km of the study reach was also captured by the model. This result proved that the two-dimensional mixing and settling model with flocculation was a suitable model for the sediment propagation in Porong River.
Keywords: flocculation; sediment concentration; field measurement; two-dimensional mixing and settling; mud volcano